USP7 promotes temozolomide resistance by stabilizing MGMT in glioblastoma - Jiabing Li; Xiaorong Feng; Zhaohui Liu; Yunfang Deng; Zhiming Sun; Bei Chen; Lihui Wu; Xiaolong Wang; Lin Miao; Liyuan Zeng; Lei Hu; Yuming He; et al. (Cell Death and Disease)
Abstract Glioblastoma (GBM), a World Health Organization (WHO) grade IV glioma, is one of the most lethal brain tumors, with a poor prognosis and limited treatment options. Temozolomide (TMZ), a first-line chemotherapeutic agent, often proves ineffective due to resistance and toxicity associated with overexpressed O 6-methylguanine-DNA-methyltransferase (MGMT). In this study, we identified ubiquitin-specific protease 7 (USP7) as a nuclear regulator of MGMT stability and TMZ resistance. USP7 binds directly to MGMT via its UBL domain, counteracts K48-linked ubiquitin chains, and prevents MGMT proteasomal degradation. This functional relationship is further supported by their nuclear colocalization. Strikingly, this study, together with previous findings, establishes USP7 as a key integrator of all three major alkylation repair pathways through its role in stabilizing alkylation repair proteins. USP7 stabilizes MGMT through a dual mechanism, thereby modulating the direct reversal repair pathway. Inhibition or knockdown of USP7 reduces MGMT levels, as well as those of XPC, ALKBH2, and ALKBH3, impairs DNA repair capacity, and sensitizes GBM cells to TMZ, enabling effective treatment with reduced TMZ dosages. Clinically, tissue microarray analyses reveal that USP7 and MGMT co-overexpression in GBM correlates with poor patient survival. Collectively, our results uncover a new and direct role for USP7 in MGMT-mediated direct reversal repair and TMZ resistance, positioning USP7 as a distinctive integrator of alkylation repair pathways. Targeting USP7 provides mechanistic insights into regulating diverse alkylation repair pathways and offers a strategy to enhance the efficacy of combination chemotherapies, including TMZ and other alkylating agents, by modulating distinct repair mechanisms in GBM.